Reconstructive strategies following Fournier’s gangrene: A retrospective analysis of outcomes - Boynuyoğun, Etkin (Acta Medica, 2026)
Objective: Fournier’s gangrene is a rapidly progressive and necrotizing infection of the perianal region and scrotum. Once clinical stabilization is achieved, the delayed reconstruction of the resultant defects can be planned. This study presents our institutional experience with reconstruction after Fournier’s gangrene and discusses various surgical approaches along with their respective advantages and limitations. Materials and Methods: A total of 21 patients were included in the study. The patients included in this study were older than 18 years with Fournier’s gangrene and a minimal follow-up of 6 months postoperatively. Demographic and clinical variables, including mean age, defect size and location, comorbid conditions, time interval between initial debridement and reconstruction, type of reconstructive method used, postoperative hospital stay, and complication rates were analyzed. Results: A total of 21 male patients aged 42-76 years with previously performed reconstruction following Fournier’s gangrene. The defect most commonly involved the scrotum, and 68% of the scrotal skin was defective (38%–100%). Two patients had perineal involvement. Comorbidities were present in 86% of patients, most commonly diabetes mellitus. All patients received delayed surgical reconstruction after the appearance of healthy granulation tissue at the base of the wound. The mean time to reconstruction was 28.4 days (range, 15–56 days). The most commonly used reconstruction method was the scrotal flap alone (57%). The mean hospital stay after reconstruction was 7.2 days. Conclusion: Fournier’s gangrene is a rapidly progressive and fulminant necrotizing infection that requires prompt antibiotic therapy and aggressive surgical debridement. Reconstruction of soft tissue defects is essential for restoring functional and aesthetic integrity. The optimal approach should be individualized based on patient characteristics and defect features. Further comparative studies are required to refine the reconstructive strategies and improve the long-term outcomes.